Uji Antagonis Trichoderma sp dan Gliocladium sp terhadap Fusarium Penyebab Penyakit Layu pada Beberapa Jenis Tanaman Pisang di Kebun Raya Purwodadi secara in-vitro - Suharjono, Suharjono; Kurniati, Tri Handayani; Soejono, Soejono; Dewi, Susanti (Universitas Atma Jaya Yogyakarta, 2004)
Purwodadi Botanical Garden has more than one hundred collection of cultivated bananas. The major problem in keeping their existency is the occuring of Fusarium wilt disease which was commonly controlled by pesticide or eradication to terminate the infectious cycles. Trichoderma and Gliocladium were frequently used as antagonist fungus in controlling the Fusarium wilt disease in kenaf, tomato or the other plants. So, this study aims was to know the potency of Trichoderma and Gliocladium on Fusarium growth inhibition. The experimental design was done by Randomized Complete Design Factorial using three factors i.e. antagonist fungus, Fusarium and growth distance. The level of retardation was measured by the growth distance of Fusarium that interacted to antagonist fungus and data analysis were conducted by Analysis of Variance (ANOVA). The results showed that Trichoderma has higher inhibition than Gliocladium and the highest inhibition occurred at 1 cm distance of inoculum which was performed on Fusarium 4 (77.78%). There was not any significant differencies between Fusarium 1 with Trichoderma (73.55%) and Fusarium 2 with Gliocladium (73.33%). At 2 cm distance, the highest inhibition occurred in Fusarium 3 by Trichoderma (72.71%), which was not significantly different with Fusarium 1, 2 and 4. While at 3 cm distance, the highest inhibition on Fusarium 4 by Trichoderma was 51.11% and not significantly different from Fusarium 1, 2 and 3.